Effects of Long-Term Oral Administration of N-Palmitoylethanolamine in Subjects with Mild Cognitive Impairment: Study Protocol - Michela Bossa; Ornella Argento; Chiara Piacentini; Nicola Manocchio; Lucia Scipioni; Sergio Oddi; Mauro Maccarrone; Ugo Nocentini (Brain Sciences, 2023)
N-palmitoylethanolamine (PEA) plays a key role in preventing Aβ-mediated neuroinflammation and neurotoxicity in murine models. It has been demonstrated that PEA provides anti-neuroinflammatory, pain-relieving and neuroprotective actions even in humans. In this project, we aim to evaluate these anti-neuroinflammatory effects via the cognitive evaluation and biochemical analyses of a 12-month oral administration of PEA in subjects with mild cognitive impairment (MCI). Subjects with MCI will be randomized to placebo or PEA groups, and followed for another 6 months. Cognitive abilities and neurological inflammation will be examined at baseline and after treatment. The specific objectives of the project are to ascertain whether: (i) PEA influences the scores of the neuropsychological and behavioral evaluations after one-year treatment, comparing PEA-treated and placebo subjects in both MCI and control groups; (ii) PEA can change the inflammatory and neuronal damage markers of blood and urine in MCI subjects; and (iii) these changes correlate with the clinical scores of participating subjects.